PALYNOLOGY OF TÖGI NDRAWA CAVE,COASTAL AREA OF NIAS ISLAND, NORTH SUMATERA - A.A Polhaupessy (Marine Geological Institute of Indonesia, 2009)
Environmental study of the Tögi Ndrawa Cave by means of pollen analysis has been carried out. The interpretation is made based on the occurring pollen types as guide, the resulted pollen spectra, and curves exhibited in the pollen diagram. Combined evidences obtained from the palynological, geological and archaeologi cal studies provide the basis for the interpretation of plant ecology of shore and further the vegetational history of the marine area. In the meantime, plant ecology itself is concerned not only with plant communities but also the interaction among the plants involved, and their environmental factors. Keyword: Environmental, Pollen Analysis, Tögi Ndrawa Cave Studi lingkungan GuaTögi Ndrawa, Pulau Nias, telah dilakukan dengan menggunakan analisis polen. Interpretasi ini berdasarkan hadirnya jenis polen sebagai petunjuk dalam membentuk diagram polen. Hasil studi palinologi, geologi dan arkeologi telah menghasilkan interpretasi dasar mengenai ekologi tumbuhan pantai kemudian sejarah tumbuhan yang pernah tumbuh didaerah laut dangkal. Pada zaman ini, ekologi tumbuhan tidak hanya tergantung komunitas tumbuhan tetapi justru tergantung pada interaksi diantara komunitas tumbuhan dan faktor lingkungannya. Kata Kunci: Lingkungan, Analisis polen, Gua Tögi Ndrawa